Climate–urban nexus: A study of vulnerable women in urban areas of KwaZulu-Natal province, South Africa - Hlahla, Sithabile; Simatele, Mulala Danny; Hill, Trevor; Mabhaudhi, Tafadzwanashe (Weather, Climate, and Society, 2022)
The changes in climatic conditions and their associated impacts are contributing to a worsening of existing gender inequalities and a heightening of women’s socioeconomic vulnerabilities in South Africa. Using data collected by research methods inspired by the tradition of participatory appraisals, we systematically discuss the impacts of climate change on marginalized women and the ways in which they are actively responding to climate challenges and building their adaptive capacity and resilience in the urban areas of KwaZulu-Natal, South Africa. We argue that changes in climate have both direct and indirect negative impacts on women’s livelihoods and well-being. Less than one-half (37%) of the women reported implementing locally developed coping mechanisms to minimize the impacts of climate-related events, whereas 63% reported lacking any form of formal safety nets to deploy and reduce the impacts of climate-induced shocks and stresses. The lack of proactive and gender-sensitive local climate change policies and strategies creates socioeconomic and political barriers that limit the meaningful participation of women in issues that affect them and marginalize them in the climate change discourses and decision-making processes, thereby hampering their efforts to adapt and reduce existing vulnerabilities. Thus, we advocate for the creation of an enabling environment to develop and adopt progendered, cost-effective, transformative, and sustainable climate change policies and adaptation strategies that are responsive to the needs of vulnerable groups (women) of people in society. This will serve to build their adaptive capacity and resilience to climate variability and climate change–related risks and hazards. © 2022 American Meteorological Society.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afrique du sud; approches et analyses; changements climatiques; environnement; histoire et politique; patriarcat; pauvreté; projet charge mentale; périodes historiques; régions géographiques; système colonial; systèmes d'oppressions; thématiques

Le contrat sexuel - Pateman, Carole (La Découverte Poche, 2022)
« Par quel étrange paradoxe le contrat social, censé instituer la liberté et l'égalité civiles, a-t-il maintenu les femmes dans un état de subordination ? Pourquoi, dans le nouvel ordre social, celles-ci n'ont-elles pas accédé, en même temps que les hommes, à la condition d'« individus » émancipés ? Les théories du contrat social, héritées de Locke et de Rousseau, et renouvelées depuis Rawls, ne peuvent ignorer les enjeux de justice que soulève le genre. Carole Pateman montre, dans cet ouvrage désormais classique, que le passage de l'ordre ancien du statut à une société moderne du contrat ne marque en rien la ﬁn du patriarcat. La philosophe met ainsi au jour l'envers refoulé du contrat social : le « contrat sexuel », qui, via le partage entre sphère privée et sphère publique, fonde la liberté des hommes sur la domination des femmes. Il s'agit là moins d'exploitation que de subordination, comme le démontre l'autrice en analysant le contrat de mariage, mais aussi l'ensemble des contrats touchant à la propriété de la personne, de la prostitution à la maternité de substitution, jusqu'à l'esclavage et au salariat. Ainsi s'engage, à partir du féminisme, une critique de la philosophie politique libérale dans son principe même : pour Carole Pateman, un ordre social libre ne peut en aucun cas être de type contractuel. »-- Quatrième de couverture.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; histoire et politique; incontournable; justice sociale; outils; ouvrages de références; patriarcat; phi4336; philosophie; philosophie politique; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; théories féministes; violences; états-unis

Gender, climate breakdown and resistance: The future of human rights in the shadow of authoritarianism - Rosamond, Annika B.; Davitti, Daria (Nordic Journal of Human Rights, 2022)
In this article we examine the future of human rights by looking at how ‘authoritarianism’, in its multifaceted forms and manifestations, intersects with existing discourses on climate change, environmental protection, populism and ‘gender deviance’. By adopting an intersectional lens, we interrogate the emergence of the right to a healthy environment and reflect on whether it will help against the double challenge faced by human rights: of climate breakdown and rising authoritarianism. We study the link between authoritarianism and populism, focusing on far-right populism and the creeping authoritarian features that we can associate with far-right groups, both movements and parties. We also consider how certain understandings of nature and the environment are put forward by authoritarian regimes. This leads us to consider so-called ‘ecologism’ and the ways in which far-right movements draw upon green thought on the natural environment to further a gendered agenda based on conceptions of nature as a ‘national treasure’. These conceptions, as we demonstrate, go hand in hand with policies that promote national identity and directly undermine the rights of migrants, ethnic minorities, women and LGBT+ groups. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; capitalisme; changements climatiques; discipline; droits des femmes*; droits humains; environnement; histoire et politique; intersectionnalité; patriarcat; populisme de droite; projet charge mentale; périodes historiques; racisme; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques; écologisme d'extrême-droite

Le privilège de dénoncer: justice pour toutes les victimes de violences sexuelles - Souffrant, Kharoll-Ann; Diallo, Rokhaya (Les éditions du remue-ménage, 2022)
''Le privilège de dénoncer cherche à savoir pourquoi les femmes et les filles noires sont largement absentes du débat public lorsqu'il est question de violences sexuelles. Kharoll-Ann Souffrant explore sans détour les raisons historiques de ce constat à partir d'exemples tirés du Québec, de la France et des États-Unis. Entre les impacts actuels de la colonisation et de l'esclavage, les stéréotypes liés à la sexualité des Noir·es ainsi que les failles du système de justice criminelle, l'autrice assemble les pièces du casse-tête pour révéler les dynamiques à l'œuvre derrière la marginalisation des femmes afrodescendantes. La parole des survivantes noires serait-elle doublement invisibilisée, tant par les institutions patriarcales que par un certain féminisme blanc et libéral qui aurait accaparé le mouvement #MeToo? Une invitation à élargir sans délai notre compréhension des violences sexuelles et racistes, et ce, pour le bénéfice de l'ensemble de la société. «Dans un Québec qui – comme tant de sociétés – s'élance encore d'un pas hésitant lorsqu'il s'agit de confronter le racisme systémique, la parole de Kharoll-Ann Souffrant est précieuse. Elle est une femme noire dont les racines se trouvent sur la terre où s'est érigée la première république noire au monde, à Haïti, née d'une révolution victorieuse contre la France coloniale, contre l'oppression esclavagiste. Aujourd'hui Kharoll-Ann Souffrant pose sa plume telle la digne héritière de celles et ceux qui se sont dressé·es il y a plus de deux cents ans. Avec verve, elle décrypte ce racisme conçu pour écraser ses aïeux, dont les résidus persistent à obstruer les regards qui se posent sur elle.» ''-- Site de l'éditeur.
Keywords: 2000 à aujourd'hui; 2020-2029; afro-féminisme; amériques; approches et analyses; canada; cours; discipline; féminisme afroaméricain; haïti; histoire et politique; intersectionnalité; inégalités; patriarcat; point de vue situé; pol4212; premier cycle; périodes historiques; québec; racisme; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; travail social; témoignage; violences; violences sexistes et sexuelles; violences sexuelles